2018
DOI: 10.1055/a-0723-2807
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Parathyroidectomy on Plasma iPTH and (1–84) PTH Levels in Patients with Stage 5 Chronic Kidney Disease

Abstract: Currently, the second-generation intact parathyroid hormone (iPTH) assay is commonly used for measuring PTH levels. The iPTH assay detects both full-length (1-84)PTH and (7-84)PTH fragments, which have antagonistic effects on (1-84)PTH in bones and kidneys. The third-generation PTH assay is specific for (1-84)PTH. This study examined the features of different PTH fragments in stage 5 chronic kidney disease (CKD) and the effects of parathyroidectomy (PTX) on the above markers in severe secondary hyperparathyroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
(55 reference statements)
1
7
0
Order By: Relevance
“…In this study, patients with PTX were followed up over three months after the surgery (median follow-up time: 6.50 months). Consistent with the previous findings [ 13 ], elevated circulating adjusted calcium, iPTH, (1-84) PTH, (7-84) PTH levels, and a decreased (1-84) PTH/iPTH ratio was alleviated after PTX in severe SHPT patients. This data showed that an improved SDNN was related with decreased (1-84) PTH and (7-84) PTH levels, while improved SDANN was related with decreased (1-84) PTH levels.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, patients with PTX were followed up over three months after the surgery (median follow-up time: 6.50 months). Consistent with the previous findings [ 13 ], elevated circulating adjusted calcium, iPTH, (1-84) PTH, (7-84) PTH levels, and a decreased (1-84) PTH/iPTH ratio was alleviated after PTX in severe SHPT patients. This data showed that an improved SDNN was related with decreased (1-84) PTH and (7-84) PTH levels, while improved SDANN was related with decreased (1-84) PTH levels.…”
Section: Discussionsupporting
confidence: 92%
“…Exclusion criteria of the patients included [ 13 , 16 ]: (1) undergoing maintenance dialysis between 0 and 3 months; (2) persistent SHPT patients who underwent PTX before enrollment and required the second PTX due to residual hyper-functional parathyroid tissue; (3) had a history of kidney transplantation; (4) a fasting blood glucose on the day of evaluation ≥200 mg/dL; (5) the presence of fever, infection or pregnant women; (6) severe congenital heart disease, atrial fibrillation or flutter, high-grade atrioventricular block, permanent pacemaker implantation; (7) severe hepatic disease, chronic obstructive lung disease, malignant tumors, or severe mental disorders; (8) episodes of acute myocardial infarction, stroke, or a major surgical procedure within the past two months; and (9) the use of immunosuppressive drugs, calcitonin, or bisphosphonates.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk of hip and/or vertebral fractures was further increased in postmenopausal women with the deterioration of kidney function [16,17]. The mainstays of therapy for CKD-MBD include dietary phosphorus restriction, phosphate binders, dialysis, calcimimetics with calcitriol or vitamin D analogs, and parathyroidectomy, which aim to restore the balance between calcium, parathyroid hormone (PTH), phosphorus and vitamin D [18,19].…”
Section: Introductionmentioning
confidence: 99%